Impact of electrocautery on fatigue life of spinal fusion constructs: an in vitro biomechanical study - Al Mansour, Haidara; Sonntag, Robert; Pepke, Wojciech; Bruckner, Thomas; Kretzer, Jan Philippe; Akbar, Michael (Materials, 2019)
Instrumentation failure in the context of spine surgery is attributed to cyclic loading leading to formation of fatigue cracks, which later propagate and result in rod fracture. A biomechanical analysis of the potential impact of electrocautery on the fatigue life of spinal implants has not been previously performed. The aim of this study was to assess the fatigue life of titanium (Ti) and cobalt-chrome (CoCr) rod-screw constructs after being treated with electrocautery. Twelve spinal constructs with CoCr and Ti rods were examined. Specimens were divided into four groups by rod material (Ti and CoCr) and application of monopolar electrocautery on the rods’ surface (control-group and electrocautery-group). Electrocautery was applied on each rod at three locations, then constructs were cyclically tested. Outcome measures were load-to-failure, total number of cycles-to-failure, and location of rod failure. Ti-rods treated with electrocautery demonstrated a significantly decreased fatigue life compared to non-treated Ti-rods. Intergroup comparison of cycles-to-failure revealed a significant mean decrease of almost 9 × 105 cycles (p = 0.03). No CoCr-rods failed in this experiment. Electrocautery application on the surface of Ti-rods significantly reduces their fatigue life. Surgeons should exercise caution when using electrocautery in the vicinity of Ti-rods to mitigate the risk of rod failure.